Preoperative prophylactic antibiotics in orthopaedic surgery: duration of antibiotic administration (Health Renaissance, 2013)
Background: Surgical site infection is one of the most dreaded complications faced by an orthopaedic surgeon. Objective: To find out the effect of duration of prophylactic antibiotics on the rate of surgical site infection in clean elective orthopaedic surgeries. Methods: We conducted a randomized controlled trial involving 207 clean elective orthopaedic patients undergoing surgery. The patients were divided into three groups which received intravenous prophylactic antibiotics for 24 hours, 48 hours and 48 hours followed by 7 days of oral antibiotics respectively. The patients were followed up for three months. Results: There was no significant difference in the rate of surgical site infection among the three groups. Conclusion: We conclude that there is no benefit in prolonging preoperative prophylactic antibiotics beyond 24 hours. Health Renaissance, January-April 2013; Vol. 11 No.1; 62-67 DOI: http://dx.doi.org/10.3126/hren.v11i1.7604